Factors that contribute to the sustainability of graduate education in Malaysian research-based universities - Sariman, Mohd Fathi; Tasir, Zaidatun; Hashim, Noor Hazarina (International Journal of Evaluation and Research in Education (IJERE), 2025)
Today, research is a crucial agenda of universities, and graduate education plays an important role in producing research, publications, and innovation. Thus, the quality of graduate education among Malaysian research universities must be enhanced by exploring the factors that contribute to the sustainability of graduate education. This is done systematically based on relevant literatures and experts’ opinions in graduate education. Therefore, the objective of this study is to identify factors that contribute to the sustainability of graduate education among Malaysian research-based universities (RUs). Findings demonstrate that the factors are governance of graduate education, quality of supervision, quality of programs, quality of students, research facilities, research ecosystem, and financial assistance.